2021
DOI: 10.4103/ijciis.ijciis_7_20
|View full text |Cite
|
Sign up to set email alerts
|

Statin therapy associated with decreased neuronal injury measured by serum S100β levels in patients with acute ischemic stroke

Abstract: Background: Acute ischemic strokes (AIS) are a common cause of morbidity, mortality, and disability. The serum biomarker S100β correlates with poor neurological outcomes in the setting of AIS. This study describes the impact of statin treatment on S100β levels following AIS. Methods: This was a prospective case–control study of AIS patients compared to healthy controls. Patients were stratified into three groups: (1) AIS patients on statin therapy, (2) AIS patients not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…First, the overall efficacy was statistically higher in the observation group when compared to the control group. Al-Kuraishy et al [ 24 ] pointed out in their study that the application of ROS in AIS patients has certain efficacy, which can improve the cardiac metabolism of patients and lower the risk of stroke recurrence. Lu et al [ 25 ] also confirmed the effectiveness of ROS in AIS in animal experiments, mainly reflected in the prevention of blood-brain barrier damage.…”
Section: Discussionmentioning
confidence: 99%
“…First, the overall efficacy was statistically higher in the observation group when compared to the control group. Al-Kuraishy et al [ 24 ] pointed out in their study that the application of ROS in AIS patients has certain efficacy, which can improve the cardiac metabolism of patients and lower the risk of stroke recurrence. Lu et al [ 25 ] also confirmed the effectiveness of ROS in AIS in animal experiments, mainly reflected in the prevention of blood-brain barrier damage.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Hydrophilic statins are less cross‐plasma membrane so they have less pleiotropic effects compared to lipophilic statins. 24 Of note, statins are also classified according to their nature, either natural like simvastatin and lovastatin, or synthetic like rosuvastatin. 24 Natural and synthetic statins have different pharmacokinetic properties but they have similar lipid‐lowering effects.…”
Section: Introductionmentioning
confidence: 99%
“… 24 Of note, statins are also classified according to their nature, either natural like simvastatin and lovastatin, or synthetic like rosuvastatin. 24 Natural and synthetic statins have different pharmacokinetic properties but they have similar lipid‐lowering effects. Remarkably, statins lead to a dose‐dependent effect in reducing cholesterol and LDL.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations